Patterns of use, perceptions, and cardiopulmonary health risks of cigar products: a systematic review - Comreen Vargees; Andrea M. Stroup; Taylor Niznik; Delaney Dunn; Riley Wyatt; Cosima Hoetger; Ziyad Ben Taleb; Amy M. Cohn; Caroline O. Cobb; Jessica L. Fetterman (BMC, 2023)
Abstract Objective A systematic review was conducted to evaluate the use patterns, health perceptions, and cardiopulmonary health effects of cigars. Data sources PubMed and Google Scholar were searched for peer-reviewed articles published between June 2014 and February 2021. Search keywords included cigars, cigarillos, little cigars, and cardiopulmonary health outcomes. Study selection Of 782 papers identified, we excluded non-English articles, review articles, commentaries, and those without empirical data on cigars. Three coders independently reviewed all articles and compared codes to resolve discrepancies. 93 articles met the inclusion criteria and were included. Data synthesis Cigars have evolved from premium cigars to encompass little cigars and cigarillos (LCCs). LCCs are available in an array of flavors and at a price advantage, and as a result, are used by different groups compared to premium cigars. LCCs are more frequently used by youth, young adults, and those who identify as Black/African American. LCCs are often used in combination with other tobacco products, alcohol, and cannabis. Despite limited regulation, cigars generate smoke of a similar composition as cigarettes. Among the studies identified, evidence suggests that cigar use is associated with cardiovascular and pulmonary toxicity. Higher all-cause and cancer-related mortalities are associated with cigar use, particularly with more frequent and deeper inhalation, compared to non-tobacco users. Conclusions LCCs are used more frequently by at-risk groups compared to premium cigars. Recent studies evaluating cigar cardiopulmonary health effects are limited but suggest cigars have similar health risks as conferred by cigarette smoking. With the use of LCCs and targeted marketing on the rise among high-risk groups, there is a critical need for continued research in this area.